Augmented Reality Using Real-Object Tracking Development - Sarah Olivia Meily; I Ketut Gede Darma Putra; Putu Wira Buana (Faculty of Computer Science Universitas Indonesia, 2021)
Augmented reality applications in tourism usually use images as markers, such as brochures or information boards. However, it is still ineffective because users cannot interact directly with real-objects. This study aims to create applications that more interesting and interactive way which can be used by interacting directly with real-object. This research is located in Taman Ayun Temple, one of the tourism objects that are world cultural heritage in Bali. The application is designed with the real-object tracking augmented reality method using the Wikitude Android SDK platform. The application is built in Indonesian and English. The test results show that the percentage of the recognition of 40 objects from various directions is more than 80%, from a distance of 10 to 40 meters is more than 70%, from a good and moderate lighting condition is more than 80%, and recognize similar objects as a different object.